Monthly variation in fertility, embryonic mortality and hatchability of four breeds of poultry in the Sudan - El-Jack, M.H. (1972)
(1)Hatching eggs from poultry breeds commonly used in the Sudan were weekly set from November to April for a period of three consecutive years. (2)A total number of 46,707 eggs were examined in this report. (3)It was found that both fertility and hatchability suffer seriously in March and April due to environmental temperature. (4)The overall mean fertility per cent for Fayoumi, White Leghorn, Light Sussex and New Hampshire was 89.5, 86.2, 86.5 and 76 respectively. (5)The mean hatchability percent for all eggs set was 66.6, 66.8, 65.0 and 56.7 for F., W.L., L.S. and N.H. respectively. (6)Embryonic mortality increased significantly with the increase in environmental temperature.